NOISE LEVEL IDENTIFICATION ON DENTAL CLINIC - Kamila, Izza; Noerwasito, Vincentius Totok; Samodra, Fx Teddy Badai (Journal of Vocational Health Studies, 2022)
Background: Noise is a problem affecting toothache patients psychological and physical aspects. The dental clinic can be a source of noise because it contrasts with the function of the dental clinic as a place of healing. Noise can cause toothache to be more psychologically painful, which causes dryness of the oral cavity. Purpose: Therefore, it is necessary to know how much the noise level in the dental clinic is with the case study of the Benowo dental clinic and where it comes from. Method: The researchers used an explorative method and observations to realize this activity. This study begins by calculating the clinical noise level using a sound meter, and then the results are compared with a literature study. Result: The highest noise recorded in this clinic reaches 84 dB. This is very far from the sound level recommended by SNI 03-6386-2000, which is 45 dB for dental clinics. Outside noise comes from roads, trains, and parking areas. The nature of noise from outside is sporadic, but the intensity of the noise is very high. Sources of noise from inside come from activities in the medicine room, patient conversations, drills, scaling, and compressors. Noise from within is continuous but less intense. Conclusion: The design of the dental clinic must consider the acoustic aspect as the central aspect. Further research is needed to choose the right design concept to protect the dental clinic from noise.